Nutritional profiling and sensory characterization of gluten-free, high-protein, low glycemic index of sorghum-soy baked and fried chips - Fatima, Zara; Israr, Beenish; Itrat, Nizwa; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2025)
IntroductionWheat production faces increasing threats from climate change, highlighting the need for resilient, nutrient-dense, and sustainable alternatives such as sorghum and soybeans.ObjectiveThe objective of the current study was to develop high-protein, low-glycemic, sustainable sorghum-soy snacks. The novelty of this study lies in providing a healthy snack that is gluten-free, rich in protein, and has a low glycemic index.MethodsIn this study, sorghum-soy chips were prepared using four formulations with varying proportions of soybean and sorghum flours (T0: 50:50, T1: 55:45, T2: 60:40, and T3: 65:35) and processed through baking and frying techniques. The nutritional composition, mineral profile, sensory characteristics, and glycemic index of the composite flour were evaluated to determine their functional and health-promoting potential. All the values obtained from different analyses of chips were subjected to a one-way analysis of variance (ANOVA) analysis through the software Statistix 8.1.ResultsThe sorghum-soy chips developed in this study demonstrated significant nutritional enhancement with increasing soybean incorporation. Proximate analysis revealed a marked (p < 0.05) increase in protein content, particularly in T3 (65:35 soybeans: sorghum ratio), while mineral analysis indicated appreciable levels of calcium (196.70 mg/100 g), iron (13.61 mg/100 g in T3), and magnesium (250.96 mg/100 g) among fried treatments, highlighting the potential to address micronutrient deficiencies. Sensory evaluation showed that T1 (55:45) achieved the highest scores for color, flavor, crispiness, aroma, and overall acceptability, suggesting strong consumer preference. Furthermore, baked chips displayed a lower glycemic index and reduced fat content compared to fried variants, making them more appropriate for health-conscious and diabetic individuals. In contrast, fried chips exhibited superior texture and shelf stability, emphasizing their appeal in terms of sensory quality.ConclusionSorghum-soy chips demonstrated potential as gluten-free, protein-rich, low-glycemic index snacks that promote dietary diversity and support efforts to combat malnutrition. This study provides insights into creating healthier snack options using climate-resilient crops while adhering to sustainable food system principles.